Probing Nuclear Effects at the T2K Near Detector Using Single-Transverse Kinematic Imbalance - Dolan, S; Lu, X; Pickering, L; Vladisavljevic, T; Weber, A (IOP Publishing, 2017)
In order to make precision measurements of neutrino oscillations using few-GeV neutrino beams a detailed understanding of nuclear effects in neutrino scattering is essential. Recent studies have revealed that single-transverse kinematic imbalance (STKI), defined in the plane transverse to an incoming neutrino beam, can act as a unique probe of these nuclear effects. This work first illustrates that an exclusive measurement of STKI at the off-axis near detector of the T2K experiment (ND280) is expected to distinguish the presence of interactions with two nucleons producing two holes (2p-2h) from alterations of the predominant underlying cross-section parameter (MA- the nucleon axial mass). Such a measurement is then demonstrated with fake data, showing substantial nuclear model separation potential.